GEJALA GANGGUAN BERBAHASA LISAN PADA PENDERITA BIBIR SUMBING - abdulaziz aziz (Jurnal Sastra Aksara, 2021)
Speech disorders are aspects that affect the way a person conveys speech sounds in communicating in the community. The approach used in this research is a qualitative approach. The data collection method used in this research is the method of communication with technology media. The data collection technique in this study is an online technique through zoom media (online) while the technique is recording. The data analysis method used in this study is a qualitative descriptive method. The data or results obtained in this study contained the presence of utterances that were conveyed unclearly starting from vowels and consonants. This is due to imperfect speech organs, namely the speech organs on the roof of the mouth, lips, gums and tongue and other speech tools. Finally, the sound of the language produced is not perfect.